The Effect of Composting Campus Litter Granules and Inorganic Fertilizers on the Improvement of Soil Physical Properties and Corn Yield (Zea mays L.) In Inceptisol - Maimuna La Habi; A.Marthin Kalay (Faculty of Agriculture, Pattimura University, 2021)
The addition of organic matter is done to overcome the problems that occur in acid soils such as inceptisols. The aim of the research was to develop organic fertilizer enriched in granular form from campus litter compost to improve soil physical properties and maize yield in Inceptisols. The treatments consisted of: no fertilizer (KGSK1), 8 t ha-1 granule compost (KGSK2), inorganic fertilizer (Urea, SP-36, and KCl) recommended dose (KGSK3), inorganic fertilizer + 8 t ha- granule compost (KGSK4 ), x dose of inorganic fertilizer + compost granule (8 t ha-1) (KGSK5), 2 times dose of inorganic fertilizer + compost granule 8 t ha-1 (KGSK6), x dose of inorganic fertilizer + compost granule 12 t ha- 1 (KGSK7) and 2 times the dose of inorganic fertilizer + compost 4 t ha (KGSK8). The study was designed using a randomized block design with three replications. The results of the study found that the provision of enriched campus litter granules, either applied singly or in combination with inorganic fertilizers, had a significant effect on improving soil physical properties, namely soil volume weight, soil specific gravity, soil porosity, fast drainage pores, slow drainage pores, water pores. available, and unavailable pore water were 0.90 g cm-3, 2.30 g cm-3, 7.77%, 23.54%, 8.83%, 11.62%, and 249.17%, and the yield of dry shelled corn was 7.85 tons ha- 1.Keywords: Granular compost, Corn, Inceptisol, inorganic fertilizer